PAT-7 A Natural Case Like Diabetes Rat as A New Approach on Understanding Alert of Glucose Methabolism - Adi Winarto; Komariah Komariah; Kiranadi Bambang; Manalu Wasmen; Ekowati Handharyani (Hemera Zoa, 2018)
Currently, diabetic case as a degenerative disease has widely known that it can be cure by insulin.  A remain puzzle is proliferation do not found in rest Beta cells, so insulin injection has to be applied entire life of diabetic patient. So far, there is no diagnostic approach that expresses such of thing which may indicate an early anomaly on glucose metabolism process. The aim of this research to get case model of hyperglycemic rat that has long period in process.